2005
DOI: 10.1089/hum.2005.16.792
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transduction by Recombinant Adeno-Associated Virus Vectors: Problems and Solutions

Abstract: Recombinant adeno-associated virus 2 (AAV) vectors have taken center stage owing to their potentially safer profile compared with the more commonly used retroviral and adenoviral vectors in human gene therapy clinical trials. Their remarkable versatility and efficacy in a wide variety of preclinical animal models of human diseases have attracted further attention of a number of investigators. Although two particular cell types, muscle and brain, have been shown to be highly transducible by AAV vectors, controv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…AAV serotypes have been isolated from human and various non-human primate species and many have been developed to generate a variety of recombinant AAV (rAAV) vectors. The basic biology of AAV and its associated vectors is well-studied and clinical trials are now under investigation (for reviews, see Gao et al, 2005;Grieger et al, 2006;Grimm & Kay, 2003;Hendrie & Russell, 2005;Muzyczka & Warrington, 2005;Srivastava, 2005;Warrington & Herzog, 2006;Wu et al, 2006;Zhong et al, 2006). In gene therapy, targeting of viral vectors to the correct tissues and cells is essential.…”
mentioning
confidence: 99%
“…AAV serotypes have been isolated from human and various non-human primate species and many have been developed to generate a variety of recombinant AAV (rAAV) vectors. The basic biology of AAV and its associated vectors is well-studied and clinical trials are now under investigation (for reviews, see Gao et al, 2005;Grieger et al, 2006;Grimm & Kay, 2003;Hendrie & Russell, 2005;Muzyczka & Warrington, 2005;Srivastava, 2005;Warrington & Herzog, 2006;Wu et al, 2006;Zhong et al, 2006). In gene therapy, targeting of viral vectors to the correct tissues and cells is essential.…”
mentioning
confidence: 99%
“…Therefore, it is necessary for further optimizing the experimental procedures by screening different serotypes of rAAVs (e.g. rAAV1, rAAV7 and rAAV8), using selfcomplementary double-stranded AAV vectors (scAAV), prolonging detection periods and enhancing hematopoietic cell survival to improve the efficiency of rAAV transduction and stably high expression of b-chains in vivo [34,35]. In summary, our data indicated that the rAAV2-b-globin could transduce fetal hematopoietic cells from b-thalassemia patients and mediate the stable expression of human b-globin in human hematopoietic cells in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant AAV vectors have recently attracted increased attention for the purpose of gene therapy (Asokan et al, 2006;Flotte et al, 2005;Grieger et al, 2005;Srivastava et al, 2005). Studies have shown that AAV vectors based on serotype 2 (AAV2) can introduce a broad range of cell types, including non-dividing cells, in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%